2020
DOI: 10.21203/rs.3.rs-21302/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of the Oncostatin M/ OSM receptor β axis in activating dermal microvascular endothelial cells in Systemic Sclerosis

Abstract: Abstract Background: Scleroderma (SSc) is a rare autoimmune disease characterized by vascular impairment and progressive fibrosis of the skin and other organs. Oncostatin M, a member of the IL-6 family, is elevated in SSc serum and was recognized as a significant player in various stages of fibrosis. The goal of this study was to assess the contribution of the OSM/OSMRβ pathway to endothelial cell (EC) injury and activation in SSc. Meth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…In addition, OSM protected against cardiac I/R injury by regulating apoptosis, insulin sensitivity and mitochondrial biogenesis in diabetic mice [37]. Some studies have reported that OSM activates endothelial cells [38] and smooth muscle cells [39], but to date, the role of OSM in PAH and the underlying mechanisms remain to be studied. There is an imbalance between vasodilation and vasoconstriction favouring vasoconstriction with an increase in circulating vasoconstrictors and a decrease in circulating vasodilators (i.e., prostacyclin and prostaglandin) during PAH development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OSM protected against cardiac I/R injury by regulating apoptosis, insulin sensitivity and mitochondrial biogenesis in diabetic mice [37]. Some studies have reported that OSM activates endothelial cells [38] and smooth muscle cells [39], but to date, the role of OSM in PAH and the underlying mechanisms remain to be studied. There is an imbalance between vasodilation and vasoconstriction favouring vasoconstriction with an increase in circulating vasoconstrictors and a decrease in circulating vasodilators (i.e., prostacyclin and prostaglandin) during PAH development.…”
Section: Discussionmentioning
confidence: 99%